Customer Awareness and Behavior Intention Towards the Use of Halal Logo on Restaurants - Bachok, Sabainah; Jamalluddin, Nurfattaniah; Arsat, Aliffaizi; Shahril, Aslinda Mohd; Sulaiman, Suria (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
The trend of eating out leads the food service industry to the needs of managing customers and making sure that all their needs and preferences can be fulfilled. The certification and recognition of establishment also becomes the in thing in hospitality industry, which includes the certification of halal, HACCP, and ISO. Establishment with certification is useful as a marketing strategy to attract more customers. This study discusses the level of customer awareness of towards the halal logo used in some restaurants which is carried out to give evidence to restaurant operators regarding the importance of attaching the genuine halal logo in their restaurant. From the findings, it is showed that customers are do aware of the use of halal logo on restaurants. It is also a factor in choosing a restaurant. It is concluded that halal logo is one of the main factors for customers in choosing restaurants which in return can be a main strategy to attract and retain more customers in the future, not only for the local customer but also to foreigners.